Pengembangan Gim Edukasi Jenis Tipe Data dalam Pemrograman untuk Pelajar Tingkat SMA dan SMK - William, Timothy Justin; Dirgantara, Harya Bima (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2024)
The reason behind this research is to develop an education game for student in SMA and SMK level to teach them about a concept in programming, that is data types. The researcher used Unity Game Engine and a game development framework called Game Development Life Cycle (GDLC) that comprised of 6 stages: Initiation, Pre-Production, Production, Testing, Beta, and Release. Development of the game only use assets that is free and/or made by researcher. The output of this research is a game called “Mari Berdata” that can be played for free on Desktop platform like PC or laptop. Respondents of Beta phase has also mentioned that they learn something new about data types after playing “Mari Berdata”.